Enhancement of Antioxidant Enzymatic Defenses in Salt-Adapted Rice Seedlings - Giuseppe Forlani (Agriculture)
While a rapid activation of antioxidant defense mechanisms following the exposure to salt stress has been widely reported in plants, less is known about their role under prolonged ionic stress conditions. This study aimed at investigating whether increased levels of enzymatic antioxidants are required in salt-acclimated plants. Rice, a staple crop for more than half of the world’s population, is very sensitive to excess salt, mainly at the seedling stage. The levels of selected antioxidant enzymes and the non-enzymatic antioxidant glutathione were measured in seedlings of a group of five Italian rice cultivars showing a natural variability in the susceptibility to a moderate saline environment. Up to 15.62 dS/m, the presence of salts caused a progressive growth inhibition, yet thiobarbituric acid reactive substance levels did not significantly increase. Accordingly, chlorophyll content appeared unaffected, suggesting successful acclimation. Immunological analysis showed increases of catalase protein levels in shoots, and of Cu/Zn- and Mn-dependent superoxide dismutases in both roots and shoots, whereas no variations were found for other enzymes. Only slight differences in glutathione content were evident between salt-grown seedlings and untreated controls. The data suggest that an enhancement of antioxidant defenses in different tissues takes place in rice plants to cope with sublethal salt stress conditions.